Procedural sedation and analgesia versus nerve blocks for reduction of fractures and dislocations in the emergency department: A systematic review and meta‐analysis - Maybritt I. Kuypers; Lars I. Veldhuis; Francis Mencl; Anne vanRiel; Wendy A. M. H. Thijssen; Ellen Tromp; J. Carel Goslings; Frans B. Plötz (Journal of the American College of Emergency Physicians Open)
Abstract Background Procedural sedation and analgesia (PSA) and peripheral nerve blocks (NBs) are techniques to manage pain and facilitate reduction of dislocated joints or fractures. However, it is unclear if either approach provides any distinct advantage in the emergency department (ED). The aim of this systematic review is to compare these 2 techniques on pain scores, adverse events, patient satisfaction, and length of stay (LOS) in the ED. Methods We performed an electronic search of MEDLINE, EMBASE, and the Cochrane Library, and references were hand‐searched. Randomized controlled trials (RCTs) comparing PSA with NBs for orthopedic reductions in the ED were included. Outcomes of interest included pain scores, adverse events, patient satisfaction, and LOS in the ED. A total of 2 reviewers independently screened abstracts and extracted data into a standardized form. The Cochrane risk‐of‐bias tool was used to evaluate study quality. The Grading of Recommendation Assessment Development and Evaluation approach was used to assess the certainty and strength of the evidence. Data on pain scores were pooled using a random‐effects model and are reported as standardized mean differences (SMDs) with 95% confidence intervals (CIs). Results A total of 6 RCTs (n = 256) were included in a qualitative review, and 4 RCTs (n = 101) were included in the meta‐analysis. There was no significant difference in pain scores between the PSA and NB groups (P = 0.47; SMD, 0.45; 95% CI, −0.78 to 1.69; I2 = 0.94). There were less adverse events in the NB group (0%–3.3%) compared with the PSA group (0%–20%; n = 256). LOS times were consistently shorter in the NB group (n = 215). Patient satisfaction was comparable in both groups (n = 196). Conclusion Based on the available evidence, NBs performed by emergency physicians are as effective as PSA in managing pain during orthopedic reductions in the ED. NBs are associated with fewer adverse events and shorter LOS in the ED. The quality of evidence is low.